2009
DOI: 10.1200/jco.2008.18.7815
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Safety and Efficacy of Motesanib in Patients With Progressive or Symptomatic, Advanced or Metastatic Medullary Thyroid Cancer

Abstract: Although the objective response rate was low, a significant proportion of MTC patients (81%) achieved stable disease while receiving motesanib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
172
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(183 citation statements)
references
References 33 publications
3
172
3
5
Order By: Relevance
“…Clinical development of motesanib was later taken up by Takeda. In phase II studies, the drug showed modest activity in MTC (2% PR, 81% SD) as well as in DTC (14% PR, 67% SD) patients (Sherman et al 2008, Schlumberger et al 2009). Moreover, pharmacokinetic analyses indicated that motesanib trough concentrations were lower in MTC compared to DTC patients.…”
Section: Investigational Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical development of motesanib was later taken up by Takeda. In phase II studies, the drug showed modest activity in MTC (2% PR, 81% SD) as well as in DTC (14% PR, 67% SD) patients (Sherman et al 2008, Schlumberger et al 2009). Moreover, pharmacokinetic analyses indicated that motesanib trough concentrations were lower in MTC compared to DTC patients.…”
Section: Investigational Drugsmentioning
confidence: 99%
“…Moreover, pharmacokinetic analyses indicated that motesanib trough concentrations were lower in MTC compared to DTC patients. The vast majority of patients (88%) experienced AEs, with a significant proportion (38%) of grade 3 AEs (Schlumberger et al 2009). Currently, motesanib is mostly undergoing clinical evaluation as a VEGFR, PDGFR and c-Kit inhibitor (Raghav & Blumenschein 2011).…”
Section: Investigational Drugsmentioning
confidence: 99%
“…37 Of 91 patients with progressive or symptomatic MTC who initiated therapy, only 2% had confirmed partial response but another 47% experienced stable disease for at least 24 weeks. 36 Unexpectedly, the maximum and trough plasma concentrations of the drug in MTC patients were lower than reported with other solid tumor patients, and these differing pharmacokinetics may have contributed to the lower response rate. In an analysis of biomarkers, a greater than 5.3-fold increase in concentration of placental growth factor after 3 weeks of therapy was predictive of an increased likelihood of objective response across the two cohorts.…”
Section: Motesanibmentioning
confidence: 90%
“…On the basis of this phase I experience, a multicenter, open-label phase II trial was initiated, testing the efficacy of motesanib in separate cohorts of patients with progressive DTC 35 and patients with progressive or symptomatic MTC, 36 starting at 125 mg daily. The eligibility criterion of progression was based upon serial radiographic imaging studies within the preceding 6 months, applying RECIST response assessment.…”
Section: Motesanibmentioning
confidence: 99%
“…Motesanib demonstrated activity against metastatic medullary thyroid cancer, with 81% of disease stabilizations [54], and in GIST [55]. In advanced NSCLC patients, motesanib combined with carboplatin/paclitaxel resulted in modest clinical benefit in terms of PFR and ORR, and in increased toxicity leading to study discontinuation in patients with squamous histology [56].…”
Section: Motesanibmentioning
confidence: 99%